Avaliação da estabilidade e adsorção de CO2 em estruturas metalorgânicas - Coelho, Juliana Amorim (2016)
For the development of any adsorption process, it is important that the adsorbent presents a good adsorption capacity and high selectivity for the target adsorbate. Metal-organic frameworks (MOFs) are formed by metals or metal oxides and organic linkers that bond together to generate crystalline networks. The wide variety of metals, organic linkers and synthesis methodologies allows for the design of materials with different structures and properties. For CO2 separation processes, thermal stability and moisture stability are critical properties that must be taken into account. MOFs CuBTC and MOF-74(Mg), for example, have the highest reported CO2 uptakes, but both suffer from surface area reduction and/or loss of crystallinity when exposed to water. In this work, a study of the stability on three commercial MOFs (Basolite® F300, C300 and A520) was performed. The thermal stability of the materials was assessed by thermogravimetric analysis (TGA), temperature programmed X-ray diffraction (TXRD) and adsorption equilibrium isotherms of CO2 and CH4 after degassing at different temperatures. The water stability was evaluated by adsorption equilibrium isotherms of water measured in this work and from literature. Basolite® A520, a recently synthetized aluminium fumarate MOF, showed a high stability to water and it was the adsorbent chosen for further experimental and theoretical study in processes involving CO2 adsorption, purification of natural gas and biogas (separation CO2/CH4) and flue gas (separation CO2/N2), on presence and absence of water. The experimental studies were developed using gravimetric and dynamic methods. The adsorption capacity of CO2, CH4 and N2 at 303 K and 1.0 bar was 2.1, 0.77 and 0.21 mmol/g, respectively, and the CO2 adsorption capacity remained constant after exposure to humidity and regeneration. The isosteric heats of adsorption were 21, 15, 14 and 44 kJ/mol for CO2, CH4, N2 and H2O, respectively. Fixed bed experiments were performed at 303 K to determine breakthrough curves of CO2, water vapor and CO2/water vapor mixture. Binary breakthrough (CO2/H2O) indicated a reduction of only 17% in CO2 adsorption capacity for a stream with 14% RH. Binary experiments with mixtures CO2/CH4 and CO2/N2 indicated CO2 selectivity for both separation processes. Molecular simulation studies were performed in this MOF to evaluate CO2 and N2 adsorption capacity individually and in the presence of water. A molecular model was developed to obtain fundamental adsorption data. The model was validated by experimental data reproducing previous breakthrough experiments of CO2/H2O adsorption mixture. We found that H2O has fixed adsorption sites whereas CO2 and N2 are distributed more evenly through the pores of the MOF. As the amount of water increases, clustering occurs next to the Al-O-Al-O centers of the MOF framework. Consideration of sitting and segregation of the molecules inside the pores helps explain changes in CO2 selectivity in the presence of water. The results indicate that the presence of water increases the selectivity of CO2 over N2, however, does not interfere in selectivity of CO2 over methane.